2005
DOI: 10.1097/01.ccm.0000189939.10881.60
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of point-of-care testing for glucose measurement in critically ill adults*

Abstract: The magnitude of the differences in the glucose values offered by the four different methods of glucose measurement led to frequent clinical disagreements regarding insulin dose titration in the context of an insulin infusion protocol for aggressive glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
273
3
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(299 citation statements)
references
References 13 publications
3
273
3
16
Order By: Relevance
“…Similar to Kanji et al 7 and Lacara et al, 8 we found that finger edema did not help explain differences between POC and laboratory glucose values (P = .54). Several reasons may account for the lack of difference with study 8 did researchers seek to determine if the 2 POC blood sources (catheter, fingerstick) yielded equivalent blood glucose levels.…”
Section: Poc Vs Laboratory Glucose Valuessupporting
confidence: 77%
See 3 more Smart Citations
“…Similar to Kanji et al 7 and Lacara et al, 8 we found that finger edema did not help explain differences between POC and laboratory glucose values (P = .54). Several reasons may account for the lack of difference with study 8 did researchers seek to determine if the 2 POC blood sources (catheter, fingerstick) yielded equivalent blood glucose levels.…”
Section: Poc Vs Laboratory Glucose Valuessupporting
confidence: 77%
“…Confounding factors identified in earlier studies include pH, shocklike states, hypoxemia, hematocrit level, vasopressor use, and peripheral edema. 5,7,9,10,19,20,22,[28][29][30][31][32][33][34] Hoping to use the results of our study to affect the way POC testing is done in our unit, we selected 2 of these variables to evaluate, because POC testing finger edema: the limited number of high scores for edema in our study (<25% of patients had scores of 3+ or 4+), poor interrater reliability in scoring of edema, and a lack of effect of edema on POC and laboratory differences.…”
Section: Effect Of Hematocrit and Peripheral Edemamentioning
confidence: 99%
See 2 more Smart Citations
“…Direct comparison between the laboratory and a blood gas analyser with both in the laboratory is required. Arterial samples have been shown to be more reliable; venous blood may be contaminated by glucose infusions, producing a different concentration throughout the sample, and capillary samples may be affected by poor perfusion [4,18].…”
Section: Discussionmentioning
confidence: 99%